Mephisto in the Third Reich : literary representations of evil in Nazi Germany - Barasch-Rubinstein, Emanuela, 1959- (De Gruyter Oldenbourg ; Magnes, 2015)
"The association of Nazism with the symbol of ultimate evil -- the devil -- can be found in the works of Klaus and Thomas Mann, Else Lasker-Schüler, and Rolf Hochhuth. He appears either as Satan of the Judeo-Christian tradition, or as Goethe's Mephisto. Barasch-Rubinstein looks into this phenomenon and analyzes the premise that the image of the devil had a substantial impact on Germans' acceptance of Nazi ideas"--Provided by publisher.